Strategi Komunikasi Komunitas Padang Heritage Di Era 4.0 - Sari Marta; Elva Ronaning Roem; Sarmiati Sarmiati (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The communication strategy is an important thing that must be considered by various parties. Along with the development of technology and communication in the 4.0 era, the communication strategies used have begun to be shifted by utilizing the use of social media as has been done by the Padang heritage community, which uses Instagram to disseminate the information so that it is known by a wider audience. This research used a qualitative descriptive method and was conducted in the city of Padang, with 6 informants who were members of the Padang Heritage Community. The conclusion of this study shows that in terms of designing a communication strategy carried out by the Padang heritage community on social media, Instagram also pays attention to communication components such as communicators, the channels used, audiences or targets, and the resulting feedback. In connection with this communication component, the Padang Heritage community also pays attention to the accuracy of the sources, contents, and forms of messages displayed on the Instagram @padangheritage social media account.